What is 64x^6 + 27 written as a sum of cubes?
1 answer:
Answer:
(4x² + 3)(16
- 12x² + 9)
Step-by-step explanation:
A sum of cubes factors as
a³ + b³ = (a + b)(a² - ab + b²)
64
= (4x²)³ ⇒ a = 4x²
27 = 3³ ⇒ b = 3
Hence
64
+ 27
(4x² + 3)((4x²)² - (4x² × 3) + 3²)
= (4x² + 3)(16
- 12x² + 9)
You might be interested in
Answer:
16
Step-by-step explanation:
b^2
Let b= -4
(-4)^2
16
Answer:
1/12 for each person
Step-by-step explanation:
draw a cake then cut it in half then make sure each side has six
then count all the total then each person gets 1 piece of the cake
Answer:
-11
Step-by-step explanation:
3 i believe.because well 3 yeah
![\frac{9}{x-8}=\frac{4}{5}](https://tex.z-dn.net/?f=%5Cfrac%7B9%7D%7Bx-8%7D%3D%5Cfrac%7B4%7D%7B5%7D)
Cross multiply:
![(9)(5)=(4)(x-8)](https://tex.z-dn.net/?f=%289%29%285%29%3D%284%29%28x-8%29)
Simplify:
![45=4x-32](https://tex.z-dn.net/?f=45%3D4x-32)
Group like terms:
![77=4x](https://tex.z-dn.net/?f=77%3D4x)
Solve for x by division:
![x=\frac{77}{4}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B77%7D%7B4%7D)